Assistance in the Preparation of Simple Financial Statements for the Karang Taruna of Rahayu Village, Tuban Regency - Anggapratama, Reza; Sulistyowati, Rina; Kustaji, Kustaji; Noor, Fauzian; Agustino , Muhammad Rizqi; Fadila, Esti Nur (Indonesian Scientific Journal, 2026)
This community service program aims to strengthen the capacity of the Karang Taruna of Rahayu Village, Tuban Regency, in preparing simple financial statements in a transparent and accountable manner. The activity was initiated due to limited financial literacy and the absence of systematic financial recording, which potentially hindered organizational accountability and sustainability. Proper financial administration is essential to enhance public trust and support effective youth organizational governance at the village level. The program was implemented through several stages, including needs assessment and coordination, socialization and basic financial education, technical training on simple bookkeeping, mentoring, and evaluation. Training materials focused on recording cash inflows and outflows, preparing a general cash book, organizing transaction evidence, and compiling activity accountability reports. A participatory and practice-based approach was applied to ensure that participants could directly implement the acquired knowledge. The results indicate improved understanding and skills among administrators in preparing structured financial reports. Participants demonstrated greater competence in financial recording and documentation. This program contributes to strengthening institutional governance and promoting sustainable and accountable financial management practices within the Karang Taruna organization.